الحماية الجنائية للمال العام في التشريع الجزائري - بلال لكحل (جامعة المسيلة, 2025)
The public funds, according to Algerian legislation, are understood as funds owned by the state that are used for the public benefit and expended in accordance with laws. Public funds differ from private funds, as the latter are owned by individuals or non-governmental entities. Public funds are allocated for the public interest, either for direct public use or to serve public facilities. Public funds are acquired through ordinary means such as contracts or donations, as well as through exceptional means, such as transfer of assets, with the approval of the Algerian legislature in accordance with the United Nations Convention. To prevent and combat corruption, the Algerian legislature has introduced a law related to the prevention and fight against corruption. This law establishes institutional mechanisms aimed at preventing and combating corruption, such as the Central Office for Combating Corruption and the Supreme Authority for Transparency, Prevention, and Fight against Corruption. The law also sheds light on crimes that affect public funds, such as embezzlement of public funds and bribery. To deter these crimes, the legislature has enacted measures for monitoring and imposing penalties for each offense.